2021
DOI: 10.1108/wwop-08-2020-0044
|View full text |Cite
|
Sign up to set email alerts
|

The relationships among self-efficacy, health literacy, self-care and glycemic control in older people with type 2 diabetes mellitus

Abstract: Purpose This study aims to identify the relationships among self-efficacy, health literacy, self-care and glycemic control in older people with type 2 Diabetes Mellitus (DM). Design/methodology/approach This study was a descriptive analytics correlational study with a cross-sectional design. The sampling method was purposive sampling involving 68 older people with type 2 DM. Findings The results showed that self-efficacy, health literacy and self-care correlated with glycemic control at significant levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…Thus, self-efficacy is a key psychosocial factor that seems to lead to better adherence in diabetes management. Supporting this view, several studies have reported a significant relationship between self-efficacy and self-care behaviors influencing glycemic control in the T2D population (Al-Khawaldeh et al, 2012;Amer et al, 2018;Brown et al, 2016;Saleh et al, 2021;Sharoni & Wu, 2012).…”
Section: Introductionmentioning
confidence: 86%
“…Thus, self-efficacy is a key psychosocial factor that seems to lead to better adherence in diabetes management. Supporting this view, several studies have reported a significant relationship between self-efficacy and self-care behaviors influencing glycemic control in the T2D population (Al-Khawaldeh et al, 2012;Amer et al, 2018;Brown et al, 2016;Saleh et al, 2021;Sharoni & Wu, 2012).…”
Section: Introductionmentioning
confidence: 86%
“…Health literacy and medication adherence are strongly associated. Poor glycemic control due to low-health-literacy among diabetes patients reported to both South-East Asian and Middle Eastern countries [45][46][47][48][49][50][51].…”
Section: Patientsmentioning
confidence: 99%
“…Health literacy and medication adherence are strongly associated (Table 1). Poor glycemic control due to low-healthliteracy among diabetes patients reported to both South-East Asian and Middle Eastern countries [45][46][47][48][49][50][51].…”
Section: Barriers Of Adherence Among Diabetes Patientsmentioning
confidence: 99%